Influence of rotor excitation source model in electromagnetic field–circuit coupling analysis model of tubular hydro‐generator on no‐load voltage waveform and damper winding loss calculation results - Shi‐fu Gu; Zu‐ying Bian; Zhi‐ting Zhou; Zhen‐nan Fan; Yong Yang; Jing‐can Li (IET Electric Power Applications, 2023)
Abstract In this study, a 34‐MW tubular hydro‐generator was selected as the study example. For the electromagnetic field–circuit coupling analysis model, the effects of the ideal DC voltage and current sources (i.e. two models of the rotor excitation power supply) on the no‐load voltage waveform quality and the damper winding loss calculation results were studied by considering the influence of the electromagnetic induction of the rotor excitation winding. The obtained results provide direct and effective theoretical support and technical reference for improving the accuracy and rationality of the calculation results of the electromagnetic performance parameters and the analysis, design, manufacturing and operating level of such generators.